Impact of cluster-based technology transfer on profitability of ginger cultivation by small hill farmers of Shivalik region of Haryana: Impact of cluster-based technology transfer in ginger - Grewal, S S; Kanwar, J S (Journal of Spices and Aromatic Crops, 2022)
Ginger (Zingiber officinale) is an important commercial crop of Morni hills of Haryana Shivaliks. There was considerable gap between the actual yield and income than the potential indicated by successful growers. In an attempt to bridge this gap by adopting a cluster development approach, 32 ginger growers of a hill village were formed as a common group to implement the recommended package of practices based on soil test analysis and adopted over one bigha (1/12th of hectare) of 32 demonstration plots and one bigha was kept as untreated control with farmers’ normal practice. The beneficiary farmers were provided trainings, exposure visits and interaction with agricultural experts. The average fresh ginger rhizome production in treated plots was 11.19 t ha-1 as against 6.97 t ha-1 in control plots. While 84 percent farmers obtained an yield of 11 to 12 t ha-1, yield recorded by remaining farmers ranged from 7.44 to 9.63 t ha-1 thus indicating scope of further increase in production. The ratio between seed used and rhizome yield was taken as an indicator of yield potential and this was 4.04 in case of treated plots and 2.65 in case of control thus registering overall increase of 52.4 percent. The total gross and net returns were Rs 996678 and 395925 ha-1 and the average cost of cultivation was Rs 600753 ha-1. The overall benefit cost ratio was 1.66. However, in case of control plots, the average gross and net returns were Rs 532800 and Rs 106972 with a benefit cost ratio of 1.22. In the cluster based approach, reduction in input costs and collective marketing resulted in better dividends.